2010
DOI: 10.1126/science.1188158
|View full text |Cite
|
Sign up to set email alerts
|

Small Peptides Switch the Transcriptional Activity of Shavenbaby During Drosophila Embryogenesis

Abstract: A substantial proportion of eukaryotic transcripts are considered to be noncoding RNAs because they contain only short open reading frames (sORFs). Recent findings suggest, however, that some sORFs encode small bioactive peptides. Here, we show that peptides of 11 to 32 amino acids encoded by the polished rice (pri) sORF gene control epidermal differentiation in Drosophila by modifying the transcription factor Shavenbaby (Svb). Pri peptides trigger the amino-terminal truncation of the Svb protein, which conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
339
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(348 citation statements)
references
References 21 publications
6
339
1
2
Order By: Relevance
“…These transcripts have expression levels and tissue specificity similar to the stringent lincRNA set, but a significantly higher level of sequence conservation. Many could encode small peptides, similar to those that function in Drosophila melanogaster embryogenesis (Kondo et al 2010). Another 1533 TUCP transcripts are classified as pseudogenes, and may represent pseudogenes that have evolved to function as noncoding regulatory agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These transcripts have expression levels and tissue specificity similar to the stringent lincRNA set, but a significantly higher level of sequence conservation. Many could encode small peptides, similar to those that function in Drosophila melanogaster embryogenesis (Kondo et al 2010). Another 1533 TUCP transcripts are classified as pseudogenes, and may represent pseudogenes that have evolved to function as noncoding regulatory agents.…”
Section: Discussionmentioning
confidence: 99%
“…5E,F). Thus, some of these transcripts may encode small functional peptides (Kondo et al 2010), whereas others may function as noncoding RNA.…”
Section: Novel Transcripts With Potential Coding Capacitymentioning
confidence: 99%
“…The peptides encoded by ORFs 1 to 4 of pri RNA were shown to regulate the transcription factor encoded by shavenbaby (svb) (Kondo et al, 2010), with expression of Svb target genes being greatly attenuated in pri-deficient mutants and mutation of svb resulting in an aberrant trichome pattern (Payre et al, 1999;Sucena et al, 2003;Zanet et al, 2015).…”
Section: (2) Polished Rice (Pri)mentioning
confidence: 99%
“…Although lncRNAs do not harbor apparent open reading frames (ORFs) for proteins of >100 amino acids, recent studies have identified a subset of lncRNAs that actually encode polypeptides of <100 amino acids (Fig. 1A) (Anderson et al, 2015;Kondo et al, 2010;Matsumoto et al, 2017;Nelson et al, 2016;Pauli et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The activation of Svb protein requires the truncation of its N-terminus. The details of this post-translational step are not yet completely understood, but this modification is mediated by products of the polished rice ( pri) gene, a polycistronic gene that encodes four short peptides [13]. Svb is required also for development of some of the trichomes on the adult cuticle [11] and for development of tarsal joints [14].…”
Section: Trichome Patterning Differences Betweenmentioning
confidence: 99%